rewrite the expression in the form a^n a^5xa^-3 Question rewrite the expression in the form a^n a^5xa^-3 in progress 0 Math Margaret 2 weeks 2022-01-06T22:45:02+00:00 2022-01-06T22:45:02+00:00 1 Answer 0 views 0

## Answers ( )

Answer: a^2Work Shown:

I’m assuming the “x” means “multiply”, and it is not a variable.

a^5 * a^(-3) = a^(5+(-3)) = a^(5-3) = a^2

The rule I’m using is

a^b*a^c = a^(b+c)

The base is always the same. We add the exponents.

The expression a^2 is in the form a^n with n = 2.